The Impact of Service-Learning (SULAM) On Civic Attitudes and Skills of Uthm Students - Nurul Izzati Asiyah Adam,; Maziana Mohamed, (Online Journal for TVET Practitioners, 2024)
Service learning (SULAM) is an educational approach that combinesacademic learning with meaningful community service. This study aimsto identify the effect of the service-learning program (SULAM) on theattitudes and civic skills of UTHM students. The objectives includeassessing the level of attitudes and civic skills of students before andafter participating in the program and analyzing the differences thatexist. A quantitative survey design was employed, utilizing pre- andpost-tests to measure changes in attitudes and civic skills. The studyinvolved students from the Faculty of Technical and VocationalEducation taking the subject of Sociology of Education, using the CivicAttitude and Skills Questionnaire (CASQ) as a measurement tool.Limitations of the study include respondent honesty andenvironmental factors. The findings indicate a significant increase instudents' attitudes and civic skills following the SULAM program. Thisstudy demonstrates that service learning (SULAM) effectively enhancesstudents' attitudes and civic skills, contributing to the holisticdevelopment of students and providing empirical evidence to supportthe integration of theoretical learning with practical applications inhigher education.